The unresolved ecological and evolutionary role of fungal fruit body coloration - Krah, Franz-Sebastian (Frontiers in Ecology and Evolution, 2023)
Fruit body-forming fungi are hyperdiverse and of central importance for the functioning of ecosystems worldwide. They provide habitat and resources for other organisms and perform critical roles in carbon and nutrient cycling. Like in animals and plants, fungal coloration is expected to play a fundamental role in response to biotic and abiotic environments, thus providing invaluable information to predict fungal and associated diversity in the Anthropocene. Despite centuries of plant and animal coloration research, the role of fruit body colors in fungal ecology remains mostly obscure. Essential questions are unresolved, such as: How do fruit body colors function to cope with abiotic stress? Do fruit body colors function to attract dispersal vectors or prevent predation via camouflage or aposematism? What is the significance of fruit body colors for fungal fitness? What are the implications of climate change-induced fruit body color change on fungal and associated biodiversity? Here, I review existing knowledge and outline several research trajectories to better understand the ecological role of fruit body colors. Revealing climate-driven adaptations and interactions with other organisms will improve forecasts under climate change for fungal diversity and interrelated biodiversity and inform cross-taxonomic conservation strategies.